Developmental delay in a resource-constrained environment: Screening, surveillance and diagnostic assessment - Vasantha Govender; Deshini Naidoo; Pragashnie Govender (South African Family Practice)
The range and severity of developmental delays vary, and a systematic approach to ensuring early detection for early intervention is essential. The formative years are considered critical for nurturing and maximising developmental potential. In this article, the authors describe a clinical approach to developmental delay within resource-constrained environments of South Africa. The article unpacks the history and examination, developmental screening, surveillance and diagnostic assessment and social determinants of health. For timely interventions to occur, early and accurate assessment is necessary. Medical officers and other health professionals such as nurses, general practitioners and therapists working in low-resourced contexts may use this information in their approach to the assessment of developmental delay.